A5.5 Antibodies against Domain I of β2 Glycoprotein I in Antiphospholipid Antibody Syndrome. (25th February 2013) - Chighizola, Cecilia; Pregnolato, Francesca; Grossi, Claudia; Gerosa, Maria; Norman, Gary; Mahler, Michael; Borghi, Maria Orietta; Meroni, Pier Luigi
Abstract : Background and Objectives: antibodies anti-phospholipids (aPL) react to proteins bound to PL, mainly β2glycoprotein I (β2GPI). Antibodies against β2GPI (aβ2GPI) exert a pathogenic role and represent a risk-factor for clinical manifestations of anti-phospholipid syndrome (APS). However, some aβ2GPI-positive subjects never develop APS-related clinical manifestations. This observation may be explained by the heterogeneity of aβ2GPI population, with autoantibody subgroups targeting different β2GPI epitopes. In particular, antibodies anti-domain I (aDI) but not domains IV and V (aDIV/V) of β2GPI have been associated with thrombotic events. Therefore, the aim of this study was to assess the prevalence of aDI and aDIV/V IgG in a cohort of aPL-positive patients. Material and Methods: 58 patients with a diagnosis of primary APS (PAPS) according to the 2006 Sydney criteria have been included in this study. 38 PAPS patients (65.5%) presented with venous and/or arterious thrombothic events while 20 subjects (34.5%) had obstetric manifestations only. 15 aPL asymptomatic carriers were also recruited. All samples had been tested for LA and for aCL and aβ2GPI with home-made assays according to international guidelines. In the thrombotic PAPS group, 35/38 subjects (92.1%) were aβ2GPI IgG positive; aβ2GPI IgG positivity rate was 85% in the obstetric PAPS group (17/20 women); 80% of the asymptomatic aPL carriers displayed aβ2GPI IgG. IgG specificities against whole β2GPI, DI and DIV/V have been evaluated with a novel solid-phase chemiluminiscent assay (BioFlash and ELISA, INOVA Diagnostics). Results: Out of the 73 aPL positive patients: 21% were positive for aβ2GPI, aDI and aDIV/V; 41% were positive for aβ2GPI and aDI but negative for aDIV/V; 4% were positive for aβ2GPI and aDIV/V but negative for aDI; 21% were aβ2GPI positive only; 4% were positive for aDIV/V; 9% were negative for antibodies against the whole molecule and the studied domains. The prevalence of aDI was 74% among patients with thrombotic pAPS and 60% among women with obstetric manifestations. 40% of aPL asymptomatic carriers were positive for aDI. We observed a strong correlation between aβ2GPI and aDI (p << 0.01, r = 0.836) but not aDIV/V (p = 0.07, r = 0.216). Conclusions: Most of the aβ2GPI positive sera displayed reactivity against DI, while aDIV/DV were detected in a low rate of patients. Our data suggest that DI is the immunodominant β2GPI epitope and that aDI are the main antibody population in APS patients. Future studies are warranted to better define the diagnostic and prognostic role of anti-DI in APS.